Quality assuring the professional doctorate: Challenging traditional precepts through the supervisors'/advisers' lens. Issue 3 (1st July 2019) - Abukari, Abdulai; David, Solomon
Abstract : Purpose: This paper aims to critically examine the quality of professional doctorates (PDs) from the perspective of programme supervisors in terms of how quality assurance provisions have to meet their expectations. Design/methodology/approach: The study employed an interpretative approach, using semi-structured interviews and online semi-structured questionnaire to generate data from 25 programme supervisors across universities in the UK. Data analysis and interpretation were carried out using the interactive data analysis approach (Miles and Huberman, 1994), the "bottom–up" approach to data analysis (Creswell, 2012) and the interpretative strategy recommended by Mason (2002). Four themes emerged from the data that encapsulated programme advisors' perspectives: characteristics of supervisors; opportunities in institutional quality assurance provision; challenges in quality assurance process for PDs; and supervisors' views on how quality assurance in PD can be enhanced. Findings: Quality assurance provisions have not adequately provided for the unique characteristics of PDs owing to a number of issues including lack of clarity on the philosophy and focus of PDs and conflicting perspectives among PD supervisors relating to what should ideally constitute a quality assurance process for PDs. This paper argues that to develop a relevant and robust quality assurance provision for PDs, it would be essential to ensure that the PD fundamental philosophy and focus are coherently explained. In addition, it is crucial to ensure that quality assurance provisions cover not only the academic rigor of higher level learning but also the value and potential impact of outcomes on practice and the professions. The paper also highlights a list of useful suggestions from supervisors on how to enhance quality assurance. Research limitations/implications: The research identifies a number of issues confronting quality assurance in PDs and the need for academics and policymakers to work together to deal with these to achieve the full value in PDs. As the research was based on a sample of 25 supervisors in a conference, it would be difficult and unsustainable to generalise. Hence, further research using large sample sizes of supervisors and other stakeholders based on whole programmes would be useful to achieve a sustained understanding of how quality assurance provisions of PDs have to meet expectations of the professions and professional contexts. Practical implications: To get the practical value and benefits of PDs, all stakeholders (academics, policymakers and professionals) would need to work together to ensure that appropriate quality assurance processes are developed to reflect the unique nature of the programmes. Originality/value: The paper provides a critical perspective to the current debate on quality assuring PDs from the perspective of PD supervisors who have generally been left out. It highlights issues related to quality assuring PDs, the misalignment between quality assurance provisions and the philosophy and expectations of PDs, and suggests ways through which these can be appropriately addressed to enhance quality assurance in PDs. The main contribution from this research is that it brings to the fore what supervisors, who are a part of the major players in the PD process, think about the current state of quality assurance and what can be done to make it more effective.